Secure Watermarking Technique for Color Images using Aadhar Number, DWT and SVD - Deepti Varshney (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the current situation the use of electronic devices like mobile, laptop, computer, ear phone etc has been increased in the daily routine activities specially in COVID-19. The education sector and IT industries are almost fully working in online mode in the today environment by sharing of their content in the form of digital data or multimedia data. The digital data is increasing in large scale every day and due to this increasing large amount of data, new research areas has been come introduced like bigdata, data analytic, data science etc to manage the digital data in the better or proper way. But with this the other property of digital data like its security, copyright protection, Copy control, Content authentication, Integrity verification etc. are also major concerns. The digital data or multimedia data basically includes text, images, audio, video, software etc. of individuals / organizations. Each persons or organizations are sharing his/her digital data like videos, images, messages, etc. through social media (i.e., Say namaste, Telegram, Snapchat, Instagram, WhatsApp, Facebook, etc.) to other persons or organization without any authentications. This general activity of persons has been increased in the today’s life and some persons are observing them and doing the fraud with them or misusing their digital data without his awareness. Sometimes it becomes major problems in term of legal issues. To ensure the authentication of digital data (photos), this paper proposed secure watermarking technique for color images using Aadhar number, DWT and SVD methodologies. The proposed methodology is best to protect from fraud or misuse from all type of color images shared in the public domain or globe. The experimental results are shown in different form which shows this technique is more secure and very useful for society when they are sharing their family photos in the globe.